Development and evaluation of psychoeducational resources for adult carers to emotionally support young people impacted by wars: A community case study - Vicentini, Giada; Burro, Roberto; Rocca, Emmanuela; Lonardi, Cristina; Hall, Rob; Raccanello, Daniela (Frontiers in Psychology, 2022)
Wars and armed conflicts have a devastating impact at the economic, social, and individual level. Millions of children and adolescents are forced to bear their disastrous consequences, also in terms of mental health. Their effects are even more complicated when intertwined with those of other disasters such as the current COVID-19 pandemic. To help them face such adverse events, lay adults can be supported by psychoeducational interventions involving simple tools to assist children and adolescents emotionally. Hence, we developed and implemented two public communication campaigns concerning wars to support adult carers such as parents, teachers, educators, psychologists, first responders, and others interested in young people’s wellbeing. We developed psychoeducational materials to help children and adolescents cope with negative emotions related to indirect and direct exposure to wars. This study had the objective to identify the content for two pamphlets, testing their comprehensibility, usability, and utility, and monitoring their dissemination. First, based on classifications of coping strategies and on a previous campaign about COVID-19 pandemic, we decided to include in the psychoeducational materials basic information on news about wars and common reactions to wars, respectively; on emotions that might be experienced; and on coping strategies for dealing with negative emotions. For the first pamphlet, we identified the strategies involving 141 adults. They completed an online survey with open-ended questions concerning ways to help children and adolescents cope with negative emotions associated with the Russia-Ukraine war. For the second pamphlet, we selected the contents based on Psychological First Aid manuals. Through content analyses, we chose 24 strategies. Second, data gathered with two convenience samples of adults who had consulted the psychoeducational materials supported their comprehensibility, usability, and utility. Third, we monitored the visibility of the campaigns after the release of the pamphlets, using Google Analytics™ data from the HEMOT® website through which we disseminated them. To conclude, our findings supported the comprehensibility, the usability, and the utility of the two pamphlets, to be disseminated as psychoeducational materials in the early phase of a disaster.